Liquid-liquid equilibrium of aqueous polymer two-phase systems using the modified wilson equation - Madeira, Pedro (2005)
The modified Wilson equation, developed in a previous publication, for the excess Gibbs energy of aqueous polymer solutions, is extended to multicomponent mixtures. The model provides a flexible framework to correlate and predict phase equilibria of aqueous polymer two-phase systems. The results obtained with the model are in fair agreement with the experimental data.